Self-regulatory profile scale: development and initial psychometric validation using exploratory structural equation modeling (ESEM) - Vail, Summer L. (Kansas State University, 2023)
The ability to regulate oneself, and the consequences of under-regulation, have long been an area of inquiry for many disciplines. Various domains of self-regulation have historically been studied independent of one another, despite the interactive nature and interdependent development of the domains. Currently, no quantitative measure exists that evaluates the whole of the self-regulatory system. This study seeks to confirm a factor structure of six domains of self-regulation, as proposed by the Self-Regulation Model of Attachment Trauma and Addiction (Padykula & Conklin, 2010) using exploratory structural equation modeling (ESEM). A psychometric validation of the measure was completed in two cross-sectional studies. In study 3, the measure was externally validated against a nomological network of related constructs. ESEM confirmed the use of the six pillar, 12 facet model to examine a profile of self-regulation. Clinical and research implications of the findings are discussed.
Keywords: Regulation; Coping; Exploratory structural equation modeling; Attachment; Scale development